2023
DOI: 10.1002/aro2.14
|View full text |Cite
|
Sign up to set email alerts
|

Research progress and applications of genome‐wide association study in farm animals

Abstract: Exploring the genetic loci underlying economic traits is foundational for innovation in modern animal breeding technology. Genome‐wide association studies (GWAS) have been valid and commonly used tools to dissect the genomic variants associated with phenotypes for the past ∼20 years and have contributed to our understanding of genetic and molecular bases of various traits. Here, we comprehensively review the recent research progress on GWAS methods. We highlight the methodological advancements enabled by the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 328 publications
0
1
0
Order By: Relevance
“…The cattle dataset’s sample size is larger than the pig data. Still, we believe a larger sample size will improve statistical power and enhance the ability to detect genuine associations [ 54 ]. Second, the cattle dataset may exhibit an unaccounted population structure due to the samples’ different geographic origins.…”
Section: Discussionmentioning
confidence: 99%
“…The cattle dataset’s sample size is larger than the pig data. Still, we believe a larger sample size will improve statistical power and enhance the ability to detect genuine associations [ 54 ]. Second, the cattle dataset may exhibit an unaccounted population structure due to the samples’ different geographic origins.…”
Section: Discussionmentioning
confidence: 99%
“…Their feed conversion ratio is ten times that of cattle, and the carbon emissions of broilers are only 1/10 of those of cattle 6 . Therefore, it is necessary to investigate genomic markers and genetic mechanisms related to economic traits via whole-genome sequencing to bridge the gap in production performance and accelerate breeding progress 7 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Growth traits are key in poultry breeding, and the properties of growth traits need to be considered in breeding for feed efficiency. In recent years, GWAS has been applied in poultry to explore the association between host genetics and economic traits [ 20 ]. Earlier studies identified candidate genes including NSUN3 , EPHA6 , and AGK for broilers RFI, while LAP3 was identified as a candidate gene for broiler body weight [ 21 26 ].…”
Section: Introductionmentioning
confidence: 99%